Design Approach for Thermal Performance Enhancements of a Pico‐Cell Base‐station Power Amplifier in Gallium Nitride HFET Technology - Sharma, Mihir (Université d'Ottawa / University of Ottawa, 2014)
As newer and more powerful technologies emerge in the market, the desire for compactness and aesthetics drive designers to aggressive new heights. The trend of technology is quite simply to deliver high-speed designs that pack more power while seeing reduction in form factor for ease of use at the consumer level. This presents new challenges with reliability, cost, and ultimately what the consumer strives for: performance. It is inevitable for a small compact size device, such as a smartphone or wireless repeater, to face heating issues when packing large amounts of power. The goal of this thesis is to characterize an in-market device’s thermal behavior and RF performance, and present an alternative design approach that helps improve thermal performance. This solution must not increase the design space or form factor excessively. The proposal utilizes an off-the-shelf solution and predicts performance improvements and degradation as a function of thermal performance. Electro-thermal simulators are used extensively to gauge the behavior and flow of heat within a gallium nitride device, and used as a baseline for comparison. Two modified approaches are presented and declared to be more efficient and reliable than the baseline. The design approaches comply with the industry standards of minimizing size and show a clear improvement in thermal behavior that can be utilized for any single device approach. The research is focused under similar power and biasing conditions so that designers can effectively implement a simple plug and play approach whenever the device under test is at risk of violating temperature limits and/or if performance degradation is observed under a variety of operating conditions.
Keywords: GaN; Thermal